The Analysis of Financial Invoice Automation System (IAS) Based on the Effectiveness and Efficiency in Invoice Processing at the Procurement Department: a Case Study of Company Perintis Mandiri - Anwar, Choirul (Bina Nusantara University, 2011)
Financial invoice processing is an important part of Company Perintis Mandiri’s daily business. Today, to catch up the advance of technology development, Company Perintis Mandiri has applied a new financial automatic invoice system called IAS. The scope of this research is the effectiveness and efficiency issues arose from the conversion of financial invoice processing system, from manual to automatic, and the significant differences between them. The research method used is qualitative method, study case approach. To present an objective data analysis, the writer analyzes the internal control of the financial invoice processing systems with COSO theory as the reference, by conducting interviews to the respondents. The writer also analyzes the effectiveness and efficiency between the manual and the automatic system by using a simple numerical measurement. At the end, the result of this research is important to be recognized as an input to develop, maintain, and evaluate the current financial invoice processing system used by Company Perintis Mandiri.